White Light Emission from a Simple Mixture of Fluorescent Organic Compounds - Muhamad Sarih, Norfatirah; Myers, Peter; Slater, Anna; Slater, Ben; Abdullah, Zanariah; Tajuddin, Hairul Anuar; Maher, Simon (Nature Research, 2019)
Three fluorescent organic compounds—furocoumarin (FC), dansyl aniline (DA), and 7-hydroxycoumarin-3-carboxylic acid (CC)—are mixed to produce almost pure white light emission (WLE). This novel mixture is immobilised in silica aerogel and applied as a coating to a UV LED to demonstrate its applicability as a low-cost, organic coating for WLE via simultaneous emission. In ethanol solution and when immobilised in silica aerogel, the mixture exhibits a Commission Internationale d’Eclairage (CIE) chromaticity index of (0.27, 0.33). It was observed that a broadband and simultaneous emission involving coumarin carboxylic acid, furocoumarin and dansyl aniline played a vital role in obtaining a CIE index close to that of pure white light. © 2019, The Author(s).